2013
DOI: 10.1124/jpet.113.207613
|View full text |Cite
|
Sign up to set email alerts
|

PXS-4681A, a Potent and Selective Mechanism-Based Inhibitor of SSAO/VAP-1 with Anti-Inflammatory Effects In Vivo

Abstract: Semicarbazide-sensitive amine oxidase (SSAO), also known as vascular adhesion protein-1 (VAP-1), is a member of the copperdependent amine oxidase family that is associated with various forms of inflammation and fibrosis. To investigate the therapeutic potential of SSAO/VAP-1 inhibition, potent and selective inhibitors with drug-like properties are required. PXS-4681A [(Z)-4-(2-(aminomethyl)-3-fluoroallyloxy)benzenesulfonamide hydrochloride] is a mechanism-based inhibitor of enzyme function with a pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 43 publications
0
54
0
Order By: Relevance
“…The latter effect is supported by some publications showing SSAO activity in the mouse brain both in the endothelial cells of microvessels and neurons4647. Despite the fact that a range of anti-inflammatory effects LJP-1207 have been shown in several inflammation models including colitis, multiple sclerosis, LPS-induced endotoxemia and stroke4849, it is not a suitable compound for drug development, because as a hydrazine derivative it is potentially toxic upon repeated exposure2150.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The latter effect is supported by some publications showing SSAO activity in the mouse brain both in the endothelial cells of microvessels and neurons4647. Despite the fact that a range of anti-inflammatory effects LJP-1207 have been shown in several inflammation models including colitis, multiple sclerosis, LPS-induced endotoxemia and stroke4849, it is not a suitable compound for drug development, because as a hydrazine derivative it is potentially toxic upon repeated exposure2150.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, several compounds possess unfavourable physicochemical properties, such as poor solubility, and they contain certain functional groups (e.g. hydrazine), posing potential toxicity (LJP-1207 and BTT-2052)21.…”
mentioning
confidence: 99%
“…Derivation of an alternative (haloallylamine-based) inhibitor scaffold has now led to the development of new compounds [13, 14] with different selectivity profiles to facilitate such investigations. These compounds are mechanism-based inhibitors with drug-like properties.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously demonstrated that macrophages play important roles in CS‐induced pathogenesis (Duan et al, ; Lenzo et al, ; Beckett et al, ), and their depletion prevented the development of experimental COPD (Beckett et al, ). While its effects on neutrophils has been well documented (Yu et al, ; Kiss et al, ; Foot et al, ), there has been no previously reported direct effect of alterations in SSAO activity on macrophages. The acute reduction in inflammatory cells was accompanied by significant decreases in the protein levels of the pro‐inflammatory cytokine TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…The PXS‐4728A doses used were initially based on previous studies which defined the pharmacodynamic and pharmacokinetic properties of the inhibitor. In particular, its selectivity in targeting SSAO and its bioavailability and its lack of off‐target effects (Foot et al, ; Schilter et al, ). Oral treatment also inhibited systemic SSAO activity, as determined in inguinal fat after acute CS‐exposure.…”
Section: Discussionmentioning
confidence: 99%